Organizational performance improvement strategies: An empirical study in Indonesian universities - Bambang Moertono Setiawan; Briyan Efflin Syahputra; Delly Nofiani (Universitas Ahmad Dahlan, 2025)
Bribery cases in Indonesian higher education institutions have raised serious public concern. University leaders must address this issue because bribery undermines institutional integrity and may compromise organizational performance. This study examines potential factors influencing organizational performance by focusing on the role of bribery prevention and organizational culture. It also investigates the empirical relationship between organizational culture and bribery prevention. Additionally, this current study discovers the influence of organizational culture on organizational performance through the variable of bribery prevention. The research employs quantitative research design, utilizing survey-structured questionnaires to collect data. Respondents consisted of 111 structural officials, including top-level and mid-level managers from private universities, and state universities with legal entity status, located in ten provinces across Indonesia. Data analysis employed Structural Equation Modeling through the Smart PLS. The results indicate that organizational culture has a positive impact on bribery prevention, and organizational performance. However, bribery prevention does not have a significant effect on organizational performance. Indeed, this study reveals that bribery prevention is not proven to mediate the relationship between organizational culture and organizational performance. These findings highlight the necessity of cultivating a strong organizational culture to enhance both bribery prevention measures and performance in higher education institutions.